New microbiostratigraphic data (calpionellids and calcispheres) from the tithonian of central Chile, type section (Río Tinguiririca) of the baños del Flaco Formation. (October 2022) - Kietzmann, Diego A.; Iovino, Franco; Encinas, Alfonso
Abstract: This work presents new biostratigraphic data based on calpionellids and calcareous dinoflagellate cysts for the Tithonian in Central Chile. This stratigraphic interval is mostly represented by a thick marine succession of limestone and sandstone known as Baños del Flaco Formation. This formation originated in the shallow-water setting of a carbonate ramp and correlates with other well-studied units in the Neuquén basin of Argentina. Calpionellids and calcareous dinogflagellate cysts are studied on the Chilean side of the Andes for the first time. The recognition of several calpionellids and calcareous dinogflagellate cyst species within the lower Baños del Flaco Formation allowed the identification of a preliminary microbiostratigraphic zonation. Calcareous dinoflagellate cysts include eleven species that defines the Colomisphaera tenuis, and Colomisphaera fortis zones, whereas six chitinoidellid species allowed the identification of the Chitinoidella and Crassicollaria zones, with the Slovenica, Boneti and Remanei subzones. These new microbiostratigraphic data suggest a latest early to earliest late Tithonian age for the studied interval. Highlights: First calpionellid and calcisphere biostratigraphic study for the Tithonian of Chile. Chitinoidella Zone, with Slovenica and Boneti subzones, identified for the first time in Chile. Cosmopolitan character of calpionellids and calcispheres allows to consolidate the chronostratigraphy in the Neuquén basin.